Pemberdayaan Masyarakat melalui Edukasi Budidaya Cabai dengan Media Polybag di Kampung Pedurenan Kota Bekasi - Pretty Failasufa Aziza (P3M FIA UNKRIS, 2025)
This community service activity was carried out through a student fieldwork program in Kampung Pedurenan, Kelurahan Jatiluhur, Bekasi, with the aim of empowering local residents to utilize limited yard space through the cultivation of chili plants using polybags. The program targeted housewives and local health volunteers who play a central role in family food management. The method used was a community education approach consisting of in-house training, practical workshops, and continuous mentoring. Participants were introduced to simple cultivation techniques using local materials such as soil and organic fertilizer, followed by hands-on practice and distribution of chili seedlings. The results showed an increase in participants' understanding and skills in polybag planting, along with an improvement in awareness regarding the importance of home-based food production. Community responses were highly positive, as indicated by active participation and adoption of the practices at home. The program also strengthened social bonds between students and residents, while supporting food independence at the household level. In conclusion, the program demonstrated that small-scale agricultural interventions using appropriate technology can be successfully implemented in urban settings and contribute to economic and social resilience.